Longitudinal Analysis of Risk Factors and Outcomes in Patients with Atrial Fibrillation: Stroke and Bleeding Events - Nayan Manish Gandhi; Ishan Patel; Krutarth Shukla; Nihar Gami (Wolters Kluwer Medknow Publications, 2024)
Background: "Atrial fibrillation (AF)" is a prevalent cardiac arrhythmia connected with augmented risk of stroke and bleeding events. Despite advancements in treatment strategies, managing AF remains challenging due to its multifactorial nature. Objective: This longitudinal research aimed to assess the risk factors and outcomes in subjects with AF over a specified period, focusing on stroke and bleeding events. Methods: Electronic health records of AF subjects were analyzed over a defined research period. Demographic information, comorbidities, medication history, and laboratory parameters were extracted. Stroke and bleeding events were identified, and statistical analyses were performed. Results: The research cohort comprised 800 AF subjects with a mean follow-up duration of 3 years. Significant risk factors for stroke and bleeding events included advancing age, hypertension, and anticoagulant use. The incidence of stroke and bleeding events augmented over the follow-up period, with notable differences in rates between patient subgroups. Conclusion: This longitudinal analysis provides valuable insights into the risk factors and outcomes connected with AF, particularly stroke and bleeding events. The findings underscore the importance of proactive management strategies and personalized care approaches to optimize patient outcomes in AF.